Component‐aware orchestration of cloud‐based enterprise applications, from TOSCA to Docker and Kubernetes. (28th May 2020) - Bogo, Matteo; Soldani, Jacopo; Neri, Davide; Brogi, Antonio
Summary: Enterprise IT is currently facing the challenge of coordinating the management of complex, multicomponent applications across heterogeneous cloud platforms. Containers and container orchestrators provide a valuable solution to deploy multicomponent applications over cloud platforms, by coupling the lifecycle of each application component to that of its hosting container. We hereby propose a solution for going beyond such a coupling, based on the OASIS standard TOSCA and on Docker. We indeed propose a novel approach for deploying multicomponent applications on top of existing container orchestrators, which enables managing each component independently from the container used to run it. We also present prototype tools that implement our approach, and we show how we effectively exploited them to carry out a concrete case study.